Modulation of the dynamics and cellularity of adipose tissues in different fat depots in broilers by dietary dexamethasone (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The objective of this investigation was to determine the effects of dexamethasone (DEX) on the weight and cellularity of abdominal and subcutaneous fat depots. Materials and Methods: The study was conducted on four broiler chicks (20 chicks per group) fed commercial feed and water ad libitum. The DEX was supplied with feed at 0 mg/kg (non-DEX), 3 mg/kg (DEX-1), 5 mg/kg (DEX-2), and 7 mg/kg (DEX-3) from day 0 to day 28. The entire abdominal and subcutaneous fat depots were collected and weighed after sacrificing five birds from each group on days 14 and 28. Results: The DEX groups had considerably lower (p < 0.05) fat depot weights with dose-related variation noted among the DEX groups. The histological findings revealed the presence of unilocular, round to oval-shaped adipocytes. The DEX-1 and DEX-2 had way lower (p < 0.05) numbers of adipocytes while the DEX-3 had considerably higher (p < 0.05) numbers of adipocytes than the non-DEX. DEX-1 and DEX-2 had larger (p < 0.05) adipocytes whereas DEX-3 had smaller adipocytes than the non-DEX. Adipocyte sizes and fat depot weights were found to have very strong negative relationships. Conclusion: Dietary DEX affects the growth and distribution of abdominal and subcutaneous fat depots and adipocyte cellularity subjected to both dose and duration of DEX treatment.J. Adv. Vet. Anim. Res., 9(4): 583–590, December 2022http://doi.org/10.5455/javar.2022.i627